Quality and Leadership in the Early Years : Research, Theory and Practice. - Campbell-Barr, Verity (SAGE Publications, 2015)
Do you need good leaders to achieve good quality or does good quality create good leadership? This book explores the meanings and understandings of quality and leadership that are present in early years services and how to lead in order to develop and achieve quality in your early years setting.